2003
DOI: 10.1097/00042737-200302000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucosal oxidative damage and bacterial translocation in cirrhotic rats

Abstract: Cirrhotic rats, particularly those with ascites and bacterial translocation, show increased malondialdehyde levels in ileal and caecal mucosa. These results suggest that mucosal oxidative damage in ileum and caecum could favour bacterial translocation in cirrhotic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 21 publications
5
36
1
1
Order By: Relevance
“…In this regard, increased circulating IgA and IgAIC may represent an exaggerated response of immune system to excess gut antigen exposure [34,35] , resulting from diminished mucosal integrity and spillage of IgA into the circulation. Another mechanism could involve the endotoxemia that frequently accompanies LC with PH [36] , suggested to be generated by gut flora through bacterial translocation [37,38] favored by dysfunction of intestinal barrier [33,37] . Previous literature showed that endotoxemia may decrease hepatic ASGR binding [39] .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, increased circulating IgA and IgAIC may represent an exaggerated response of immune system to excess gut antigen exposure [34,35] , resulting from diminished mucosal integrity and spillage of IgA into the circulation. Another mechanism could involve the endotoxemia that frequently accompanies LC with PH [36] , suggested to be generated by gut flora through bacterial translocation [37,38] favored by dysfunction of intestinal barrier [33,37] . Previous literature showed that endotoxemia may decrease hepatic ASGR binding [39] .…”
Section: Discussionmentioning
confidence: 99%
“…However, other aspects are still subject to investigation such as its pathogenesis [12] , diagnosis [13] and prevention [14] . Although most episodes of SBP occur in patients with advanced cirrhosis with ascites, occasionally it has been observed in non-cirrhotic patients such as fulminant hepatic failure [15] , nephrotic syndrome [16] and congestive heart failure [17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is a factor contributing to the damage of the intestinal mucosa (enabling thus BT) as well as to the development of oesophageal varices. We selected the spleen to body weight ratio of the experimental animal as a parameter suitable for the evaluation of portal hypertension (Oren et al, 1999;Dasarathy et al, 2002;Chiva et al, 2003). Chiva et al (2003) found that the values of the spleen to body weight ratio of the experimental animal in laboratory rats with liver cirrhosis caused by the application of tetrachloromethane were quite comparable with ours.…”
Section: Discussionmentioning
confidence: 60%